The Rab5A gene of marine fish, large yellow croaker (Larimichthys crocea), and its response to the infection of Cryptocaryon irritans. (July 2016) - Han, Fang; Zhang, Yu; Zhang, Dongling; Liu, Lanping; Tsai, Huai Jen; Wang, Zhiyong
Abstract: Rab GTPases, members of the Ras superfamily, encode monomeric G-proteins. Rab proteins regulate key steps in membrane traffic transport and endocytic pathway of host immune responses. Rab5A is involved in immune regulation, particularly in T cell migration and macrophage endocytosis in higher vertebrates. However, little is known of the molecular structure of Rab5A gene in marine teleost fish species and its expression profile during the parasite infection. In this study, the full-length cDNA sequence and genomic structure of Rab5A gene of the large yellow croaker ( Larimichthys crocea ) (LycRab5A), one of the most economical marine fishes, were identified and characterized. The LycRab5A protein, containing the ATPase/GTPase binding motifs and the effector molecules binding motifs, was highly homologous to that of other animals. The expression plasmid containing LycRab5A cDNA fused with GST was engineered and transformed into Escherichia coli to produce recombinant protein GST-LycRab5A, which was purified to prepare a polyclonal antibody specifically against LycRab5A. Subcellular localization revealed that LycRab5A expressed in the membrane and cytoplasm. Based on real-time PCR and Western blot analysis, we found that both mRNA and protein of LycRab5A were expressed in all tissues we examined; especially it was highly expressed in blood and gill. Interestingly, both mRNA and protein of LycRab5A were substantially up-regulated when parasitic ciliate protozoan ( Cryptocaryon irritans ) was infected. The expression of LycRab5A was reached to the maximal level at 24 h after infection. The line of evidence suggested that LycRab5A might play an important role in large yellow croaker defense against parasite infection. Moreover, on the basis of protein interaction, it was found that the LycRab5A interacted with myosin light chain (designated as LycMLC), a crucial protein in the process of phagocytosis. This discovery might contribute better understanding to the molecular events involved in fish immune responses. Highlights: LycRab5A was cloned and expressed from large yellow croaker ( Larimichthys crocea ). LycRab5A mRNA and protein were significantly up-regulated in spleen, gill and head-kidney following parasite stimulation. Rab5A was firstly reported in response to parasite infection. Subcellular localization revealed that LycRab5A expressed in the membrane and cytoplasm. LycRab5A interacted with myosin light chain (designated as LycMLC), a crucial protein in the process of phagocytosis.